A review of adaptable technologies for robotic urban horticulture - Simpson, Andrew; Harvey, Richard; Fox, Charles (Frontiers in Sustainable Food Systems, 2025)
Climate change and environmental challenges make traditional horticulture methods less reliable for future global food production. Urban horticulture offers environmental, health and social benefits, and a route to future food security, but cities provide limited access to affordable land and residents lack expertise and available time. Automation can address these challenges, but current solutions are generally prohibitive due to their scale and cost, and are focused on generating produce for premium markets. This paper explores the potential for affordable, scalable, open source autonomous robotics as a solution for automating urban environments. We specify the tasks urban horticulture robots must be able to perform and establish criteria for their scale, functions and cost. By reviewing existing robotic technologies across different domains, we explore which formats could be adapted to meet the tasks demanded by urban growers. Our focus is on small-scale vertical hydroponic farming, offering high productivity and resource savings compared to soil growing. Robots to automate these soil-free growing setups are proposed as a natural starting point for the development of urban horticulture as a future mitigation for food supply shortages amid changes to Earth’s climate and ecosystems. Finally, we identify the Open Source Hardware community as an viable route for driving the development of cost-effective, adaptable robotic solutions for urban horticulture, promoting wider adoption in capital-poor regions.